Discussion on the Selection and planning of Sewage Outfall Into the sea—a case of Gaoqi Sewage Treatment Plant. Issue 1 (August 2021) - Wang, Cui; Wang, Bingkun; Jiang, Shang
Abstract: Scientific selection of the sewage outfall into the sea plays an important role in rational utilization of Marine self-purification capacity, reduction of land sewage discharge and ecological risk, and protection of the Marine environment. In this paper, the selection and layout of the sewage outfall into the sea of Gaoqi sewage treatment plant is taken as an example. First, the primary sewage outfall is selected according to the sewage outlet selection and delimiting principle. Then, the hydrodynamic and water quality model is established to predict and analyse the effects of sewage discharge from each primary outfall on marine water quality and sensitive areas of ecological environment. Finally, the final discharge outfall is determined by considering the environmental impact, engineering economic conditions. The results show that the recommended scheme is in line with the Marine function zoning, with good pollutant diffusion conditions, far away from the ecologically sensitive areas, and with the minimum project investment.